Occupational and Patient Doses in Interventional Cardiology in Indonesia: A Preliminary Result - E. Hiswara; K.H. Ng; H. Sofyan; D. Kartikasari; N. Nuraeni (PPIKSN-BATAN, 2019)
Interventional cardiology is a branch of cardiology that manages the catheter based treatment of structural heart illnesses. These minimally invasive procedures involve inserting catheters and other devices through superficial arterial and venous access sites. Due to increased reliability and advancing technology, the number and complexity of interventional cardiology procedures haves increased in recent years. The increasing complexity of the procedures, however, require longer fluoroscopic duration, leading to increased exposure time to ionizing radiation for the patient and also for the medical staff since they need to remain close to the patient throughout the procedure. This study attempts to investigate the occupational and patient doses during the course of several interventional cardiology procedures in Indonesia, i.e. CA, PCI, cathscan, PA, PTCA, TACE, PAC and peripheral vascular. Occupational doses were measured by using individually packed three chips of TLD-100 placed in over- and under-thyroid shield used by medical staff, over- and under-apron in waist position, inside a special ‘eye-D’ holder, and inside a ring holder, while patient doses were estimated by using individually packed three TLD-100 chips attached in the x-ray tube. All TLDs were calibrated in the Secondary Standard Dosimetry Laboratory (SSDL) Jakarta. The study was performed in three big hospitals in the cities of Jakarta, Yogyakarta and Semarang. The results show that PCI procedure was the most performed one during the course of this study and gave the highest radiation doses to the staff for all type of doses calculated and measured. The maximum effective doses, eye lens doses, extremity doses, thyroid doses and gonad/ovary doses were 0.098 mSv, 0.1967 mSv, 0.7604 mSv, 0.1760 mSv and 0.0990 mSv, respectively. In the case of patient doses, the mean value of DAP for PTCA procedure of 776.76 Gy cm2 was the highest compared with those for other procedures. The results of measurement for occupational doses were in general similar to those reported by other authors, but not for patient doses that was found to be 4-5 times higher. Due to the involving of various parameters during the course of interventional cardiology procedures, it was difficult to establish a correlation between the doses received by medical staff and by the patients.